Toward a deaf translation norm - Stone, Christopher (Washington, D.C. : Gallaudet University Press, 2009)
As access for deaf people grows around the world, a new profession has begun to emerge as well, that of Deaf translators en interpreters. In this volume, Christopher Stone explores this innovation, including its antecedents and how it is manifested in public places.
Interpreting and translation -- Identity and language -- Methodology -- Role and identity -- Interpreted/translated language features -- The translation and interpretation process -- The deaf translation norm.
Includes bibliographical references (pages 177-188) and index.
Keywords: Interpreters for the deaf -- Great Britain; British Sign Language; British Sign Language; Interpreters for the deaf; Great Britain; Vertalen; Gebarentaal; Doventolken; Langue des signes britannique -- Traduction